Functional antagonism of chromatin modulators regulates epithelial-mesenchymal transition - Serresi, Michela; Kertalli, Sonia; Li, Lifei; Schmitt, Matthias Jürgen; Dramaretska, Yuliia; Wierikx, Jikke; Hulsman, Danielle; Gargiulo, Gaetano (Science advances, 2021)
Chromatin modulators with antagonistic functions on epithelial-mesenchymal interconversion regulate common pan-cancer genes. Epithelial-mesenchymal transition (EMT) is a developmental process hijacked by cancer cells to modulate proliferation, migration, and stress response. Whereas kinase signaling is believed to be an EMT driver, the molecular mechanisms underlying epithelial-mesenchymal interconversion are incompletely understood. Here, we show that the impact of chromatin regulators on EMT interconversion is broader than that of kinases. By combining pharmacological modulation of EMT, synthetic genetic tracing, and CRISPR interference screens, we uncovered a minority of kinases and several chromatin remodelers, writers, and readers governing homeostatic EMT in lung cancer cells. Loss of ARID1A, DOT1L, BRD2, and ZMYND8 had nondeterministic and sometimes opposite consequences on epithelial-mesenchymal interconversion. Together with RNAPII and AP-1, these antagonistic gatekeepers control chromatin of active enhancers, including pan-cancer-EMT signature genes enabling supraclassification of anatomically diverse tumors. Thus, our data uncover general principles underlying transcriptional control of cancer cell plasticity and offer a platform to systematically explore chromatin regulators in tumor-state–specific therapy.